GAMBARAN TINGKAT STRES KERJA TENAGA KEPENDIDIKAN UNIVERSITAS PENDIDIKAN INDONESIA - Purnamasari, Linda Mauliani; Topan, Mohamad (Journal of Economics, Accounting, Tax, and Management (JECATAMA), 2023)
This study aims to determine the level of work stress of education staff at Universitas Pendidikan Indonesia. This research method uses descriptive method with a total sample of 306 Education Staff at Universitas Pendidikan Indonesia. The results showed that the level of work stress of the Education Staff at Universitas Pendidikan Indonesia was in the medium category.